PENDEKATAN PEDAGOGIK UNTUK MENGATASI KEBERAGAMAN (KEMAMPUAN DAN GAYA BELAJAR) DALAM RUANG KELAS - Resti Hidayat; Babang Robandi; Putri Fajriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The diversity of students in the classroom, both in terms of academic ability and learning styles, is a big challenge for teachers in creating and implementing effective learning. The purpose of this study is to find out the educational methods that can be used to handle diversity so that each student can reach their best potential. Variations in ability levels, backgrounds, and learning style preferences are included in the diversity of students. To address this, a flexible and responsive approach to education is essential. The study suggests the use of